2018
DOI: 10.20945/2359-3997000000017
|View full text |Cite
|
Sign up to set email alerts
|

Preoperatively undiagnosed papillary thyroid carcinoma in patients thyroidectomized for benign multinodular goiter

Abstract: Objective: Incidental thyroid cancers (ITCs) are often microcarcinomas; among them, the most frequent histotype is the papillary one. The purpose of this study was to evaluate the rate of papillary thyroid cancer (PTC) in patients thyroidectomized for benign multinodular goiter. Subject and methods: We retrospectively evaluated the histological incidence of PTC in 207 consecutive patients who, in a 1-year period, underwent thyroidectomy for benign multinodular goiter. All patients came from an iodine-deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 65 publications
2
15
0
1
Order By: Relevance
“…A recent systematic review involving 10,743 patients with GD and 3336 non-GD patients with hyperthyroidism showed that the pooled prevalence of incidental thyroid carcinoma was 7.0% [51], which is comparable to the incidence of coincidental thyroid carcinoma of about 10% in patients who underwent thyroid surgery for any kind of benign goiter [56][57][58][59][60]. The presented series of 1808 cases showed a much lower risk with an incidental thyroid carcinoma prevalence of only 0.05%.…”
Section: Discussionmentioning
confidence: 61%
“…A recent systematic review involving 10,743 patients with GD and 3336 non-GD patients with hyperthyroidism showed that the pooled prevalence of incidental thyroid carcinoma was 7.0% [51], which is comparable to the incidence of coincidental thyroid carcinoma of about 10% in patients who underwent thyroid surgery for any kind of benign goiter [56][57][58][59][60]. The presented series of 1808 cases showed a much lower risk with an incidental thyroid carcinoma prevalence of only 0.05%.…”
Section: Discussionmentioning
confidence: 61%
“…In the end, Histopathologic examination provides a definitive diagnosis. 5,6 Previous study estimated that thyroid cancer would be the third most common cancer among women in 2019 in the USA. 6 This cross-sectional study was conducted to identify thyroid disease histopathological patterns in patients who underwent thyroid operations in our center.…”
Section: Introductionmentioning
confidence: 99%
“…They reported a mean age of 55 ± 10 years for thyroid malignancies in patients undergoing thyroidectomy for MNG. 16 The current study revealed an incidence of 8% carcinoma in MNG specimens. The incidence of thyroid malignancy in thyroidectomy specimens has been variously reported in the local data.…”
Section: Discussionmentioning
confidence: 45%